Functional Diagram of High-Precision Drive with Variables - V. A. Gane; N. T. Ahmed (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The robustness property determines sensitivity of drive quality to immeasurable deviations of its parameters and characteristics of disturbing influences. The paper shows that a standard drive has a local speed feedback in order to ensure robustness at a conversion rate. The feedback covers drive executive elements.The robustness has a special character only in respect of the straight chain conversion rate in the structure of the standard drive. Consequently, an actual problem is to ensure drive robustness in respect of other changing parameters and disturbing characteristics including characteristics of un-stationary character.